KETOKSIKAN AKUT TABLET EFFERVESCENT DARI EKSTRAK DAUN SIRIH (Piper betle L.) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Farida Hayati; Retno Murwanti; Dwi Brilyani Sandy (Universitas Islam Indonesia, 2007)
ABSTRACTA research on acute toxicity of effervescent tablet from Piper betle leaf extractum on wistaralbino male rats was done. This research aimed to determine acute toxicity potential ofeffervescent tablet from piper betle leaf extractum, evaluated clinical symptom that perhaps occurdue to the giving of effervescent tablet, single dosage orally on 24 hours to 15 days observation.The research uses male rats, which are divided into 5 groups. Group I was negative control withaquadest. Group II was given sample with 0,38 g/kgBW dosage. Then, succesively group III with1,03 g/kgBW dosage, group IV with 2,79 g/kgBW dosage and group V was given test sample withhighest dosage, that was 7,50 g/kgBW dosage. On the basis of data analysis result having beenperformed both quantitively and qualitatively, it could be said that in general, the giving ofeffervescent tablet from Piper betle leaf extractum single dosage orally on male rats from 0,38g/kgBW dosage to highest level (7,50 g/kgBW) or approximately 19,74 times of therapy dosage,didn’t cause toxic effect. It didn’t cause mortality on research animal. So we can determine thequasi LD50, that was bigger than 7,50 g/kgBW, according to Loomis criteria (1978), that acutetoxicity potential of effervescent tablet from piper betle extractum was practically not toxic category.Key words: acute toxicity, effervescent tablet, Piper betle